Proposal of a management program to improve the handling of solid waste in the district San Juan de Miraflores - Oldenhage, Frederike (2016)
One investigates in this paper: How can you improve the management of residential waste in the district of San Juan de Miraflores (SJM) concerning the environment, the waste collection and the behavior of the inhabitants? One proposes a program for the management of residential waste in SJM concentrating on the environmentally inadequate handling of waste, the insufficient waste collection service and an irresponsible and not sustainable handling of solid waste. In order to improve these points, the current situation is analyzed with data gained by field work and other sources. One suggests to separate and recycle the garbage, to improve the route, the factors “employees” and “human” for a better service of waste collection and the creation of a social consciousness to assure a responsible and sustainable handling of the domestic waste.